Signatures of plasticity, metastasis, and immunosuppression in an atlas of human small cell lung cancer - Chan, Joseph M.; Quintanal-Villalonga, Álvaro; Gao, Vianne Ran; Xie, Yubin; Allaj, Viola; Chaudhary, Ojasvi; Masilionis, Ignas; Egger, Jacklynn; Chow, Andrew; Walle, Thomas; Mattar, Marissa; Yarlagadda, Dig V. K.; et al. (Cancer cell, 2021)
Small cell lung cancer (SCLC) is an aggressive malignancy that includes subtypes defined by differential expression of ASCL1, NEUROD1, and POU2F3 (SCLC-A, -N, and -P, respectively). To define the heterogeneity of tumors and their associated microenvironments across subtypes, we sequenced 155,098 transcriptomes from 21 human biospecimens, including 54,523 SCLC transcriptomes. We observe greater tumor diversity in SCLC than lung adenocarcinoma, driven by canonical, intermediate, and admixed subtypes. We discover a PLCG2-high SCLC phenotype with stem-like, pro-metastatic features that recurs across subtypes and predicts worse overall survival. SCLC exhibits greater immune sequestration and less immune infiltration than lung adenocarcinoma, and SCLC-N shows less immune infiltrate and greater T cell dysfunction than SCLC-A. We identify a profibrotic, immunosuppressive monocyte/macrophage population in SCLC tumors that is particularly associated with the recurrent, PLCG2-high subpopulation.
Gesehen am 15.03.2022